Analysis of hearing improvement by various ossiculoplasty materials (autologous versus prostheses) in chronic otitis media patients - Faiz, Syed M.; Bhargava, Anuja; Srivastava, Saurabh; Gupta, Rajeev K.; Parveen, Mariyam; Bhatt, Kriti; Singh, Abhijeet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The main purpose of surgery in cases of chronic otitis media is to eradicate the infection and restore the middle ear hearing function. Both intact tympanic membrane and ossicular chain are essential for the restoration of hearing in these cases. The world of material science has provided otologists with array of biomaterials for middle ear reconstruction. The use of ossicular graft material in ossicular chain reconstruction has significantly improved hearing results after surgeries for chronic otitis media. Methods: The study involved a total of 50 patients presenting with dry tympanic membrane perforation with ossicular disruption and air-bone gap (ABG) of >25 from July 2014 to December 2019. The patients were randomly allotted into two groups and they underwent tympanomastoidectomy with ossiculoplasty, in one group homologous incus was used as ossiculoplasty material and in the second group Teflon TORP/PORP was used as ossiculoplasty material. Results: The present study concluded that there was no inter-group difference in post-operative hearing outcome however the two groups individually noted significant post-operative improvement in hearing. Conclusions: In present study postoperative hearing improvement was similar in both groups. Although numerous approaches to ossicular reconstruction have been proven to be successful, no single technique has received universal acceptance.